Inequality and occupational change in times of Revolution: The Tunisian perspective - Mohamed Ali Marouani; Phuong Minh Le (Global Labor Organization (GLO), 2022)
The public sector plays a large role in many developing economies, but its effect on earnings inequality dynamics has not been widely studied. In this paper, we investigate the earnings inequality trends and their determinants in the decades before and after the Tunisian Revolution, focusing on the impact of public wage and employment policy changes. A recentered-influence function (RIF) decomposition is performed to decompose the change in earnings into wage structure and composition effects and to assess the contribution of various determinants of inequality change. We find that earnings inequality decreased significantly during the period of investigation in Tunisia, mainly due to the decrease in the public-private wage gap and in sector wage gaps on the demand side, and the decreasing education premia on the supply side. The increase in marginal returns to average routine-task intensity jobs, the falling return to experience, and the decreasing regional wage gap also contributed to declining earnings inequality, but to a lesser extent.
Keywords: J21; J23; J24; J32; J45; 330; wage inequality; Revolution; occupational change; education premium; public wage policy